2008
DOI: 10.1007/s10646-008-0282-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of season on liver mitochondrial oxidative stress and the expression of HSP70 in grey mullets from contaminated estuary

Abstract: Heat shock proteins (HSPs) are the ubiquitous feature of cells in which these proteins cope with stress induced denaturation of other proteins. HSP70 is found to play a primary role in cellular defense under stress condition. In the present investigation, the seasonal impact on environmental stress induced mitochondrial HSP70 (mtHSP70) expression in the liver mitochondria was examined in grey mullets, Mugil cephalus living in the Ennore estuary (polluted site) was compared with the Kovalam estuary (unpolluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Considering that both enzymes had their activities significantly induced during warmer periods, which coincided with anabolism/biosynthesis of reserves, it is possible to sustain the occurrence of conditions more favorable to oxidative stress. This is a pattern already demonstrated for other marine fish species, including Zoarces viviparous (Heise et al, 2007), Solea senegalensis (Oliva et al, 2012), and Mugil cephalus (Padmini and Vijaya Geetha, 2009). The discussion of both biomarkers is intrinsically connected, since CAT and GSTs may give further insights into physiological oxidative processes.…”
Section: Wwwfrontiersinorgsupporting
confidence: 79%
“…Considering that both enzymes had their activities significantly induced during warmer periods, which coincided with anabolism/biosynthesis of reserves, it is possible to sustain the occurrence of conditions more favorable to oxidative stress. This is a pattern already demonstrated for other marine fish species, including Zoarces viviparous (Heise et al, 2007), Solea senegalensis (Oliva et al, 2012), and Mugil cephalus (Padmini and Vijaya Geetha, 2009). The discussion of both biomarkers is intrinsically connected, since CAT and GSTs may give further insights into physiological oxidative processes.…”
Section: Wwwfrontiersinorgsupporting
confidence: 79%
“…HSP70 could be used as a marker for assessing the biological behavior under stress in vivo [31]. It has been reported that the overexpression of liver HSP70, particularly during the summer, may confer differential effects on cell survival by protecting against changes induced by oxidative stress [32]. Our results suggest that Arg increased HSP70 mRNA and protein in the liver.…”
Section: Discussionmentioning
confidence: 51%
“…Vinagre et al (2012) also reported an important effect of temperature in the levels of oxidative stress biomarkers in the muscle of D. labrax, in a long term experience, at different temperatures. Mieiro et al (2011) reached the same conclusion analysing the brain of D. labrax and Padmini et al (2009) found that season had an important effect of the levels of oxidative stress biomarkers in the liver of the grey mullet, Mugil cephalus.…”
Section: Discussionmentioning
confidence: 54%
“…Ferreira et al, 2005;Padmini et al, 2009;Costa et al, 2011;Vinagre et al, 2012;Madeira et al, 2013). Yet, hepatopancreas, digestive gland, gills, blood and hemolymph, have also been frequently used when analysing fish, crustaceans or bivalves (e.g.…”
Section: Introductionmentioning
confidence: 99%